A new species of Acrotaphus Townes (Hymenoptera: Ichneumonidae: Pimplinae) from the Brazilian Amazon, with notes on its host spider behavioral modification - Pádua, Diego G.; Kloss, Thiago G. (Zootaxa, 2020)
Some Ichneumonidae wasps, including the genus Acrotaphus Townes, 1960 (Ephialtini: Pimplinae), induce behavioral modification in their spider hosts. Acrotaphus is a New World parasitoid wasp genus with 26 described species. This genus belongs to the Polysphincta genus group, which are ectoparasitoids of spiders of the Araneidae. In this study, we describe a new species (Acrotaphus wagnerianae sp. n.) found in the Brazilian Amazon. In addition, we discuss for the first time the behavioral modification of spiders of the Wagneriana genus (Araneidae) by wasps of the Polysphincta genus group.